The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1007/s002210050310
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cues for orientation and postural control in sighted and congenitally blind people

Abstract: This study assessed whether stationary auditory information could affect body and head sway (as does visual and haptic information) in sighted and congenitally blind people. Two speakers, one placed adjacent to each ear, significantly stabilized center-of-foot-pressure sway in a tandem Romberg stance, while neither a single speaker in front of subjects nor a head-mounted sonar device reduced center-of-pressure sway. Center-of-pressure sway was reduced to the same level in the two-speaker condition for sighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
4
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 17 publications
6
76
4
11
Order By: Relevance
“…Desta forma, indivídu-os com deficiência visual, que estão privados deste tipo de informação sensorial e, consequentemente estão mais instáveis, podem ter maior facilidade em manutenção da postura ereta correta 18 . Nesse caso, a supressão visual e a instabilidade postural são compensadas pela estimulação de outras áreas sensoriais 19 .…”
Section: Discussionunclassified
“…Desta forma, indivídu-os com deficiência visual, que estão privados deste tipo de informação sensorial e, consequentemente estão mais instáveis, podem ter maior facilidade em manutenção da postura ereta correta 18 . Nesse caso, a supressão visual e a instabilidade postural são compensadas pela estimulação de outras áreas sensoriais 19 .…”
Section: Discussionunclassified
“…), but also can originate intrinsically (i.e., the presence of developmental disabilities or degenerative conditions). Postural instability has been investigated from a perception-action approach relative to the role sensory cues play on it in older individuals (Prioli et al, 2006), in congenitally blind people (Easton, Greene, DiZio, & Lackner, 1998;Jeka et al, 1996), and in individuals with Down syndrome (Gomes & Barela, 2007).Several systems-the visual, vestibular, proprioceptive, and haptic-take part in the evolution of the postural system. In early studies of haptic sensitivity, 1 researchers focused on the acquisition of information through the exploratory actions of the hands (Cooper, Carello, & Turvey, 2000;Solomon & Turvey, 1988).…”
mentioning
confidence: 99%
“…), but also can originate intrinsically (i.e., the presence of developmental disabilities or degenerative conditions). Postural instability has been investigated from a perception-action approach relative to the role sensory cues play on it in older individuals (Prioli et al, 2006), in congenitally blind people (Easton, Greene, DiZio, & Lackner, 1998;Jeka et al, 1996), and in individuals with Down syndrome (Gomes & Barela, 2007).…”
mentioning
confidence: 99%
“…Other research has shown how the visual defect affects body perception [11][12][13][14][15][16]. Even motor development varies between sighted and blind children [17,18].…”
Section: Introductionmentioning
confidence: 99%